Rare Presentation of Small Bowel Obstruction Secondary to Intestinal Leiomyoma in a Patient with Crohn’s Disease - Benjamin J. Behers; Brett M. Behers; Ryan C. Perez; Kabir Grewal; Joe Cyriac; Joanne Makar; Russell W. Novak (Case Reports in Surgery)
Small bowel obstructions (SBOs) are surgical emergencies that can occur with mechanical blockage of the intestinal lumen. These blockages are most commonly caused by adhesions or hernias, but can also result from intestinal neoplasms. This case report documents the rare occurrence of SBO due to a submucosal leiomyoma. This case was complicated by the patient’s longstanding history of Crohn’s disease, which has a considerable overlap in symptomatology with SBOs. This may have resulted in a delay in the patient’s diagnosis. Leiomyomas should always be considered as a potential, albeit rare, cause of SBO.